Peran Religiusitas dan Psychological Well-Being terhadap Resiliensi Korban KDRT - Erna Risnawati; Alfida Arisandi; Rizki Dawanti (Fakultas Psikologi Universitas Pancasila, 2019)
Domestic violence is a case of violence that is increasing in Jakarta. Impact of domestic violence can cause deep trauma, but victims are also required to survive and have good resilience in order to continue positive life. To achieve the resilience and positive life, the victims must have a good Psychological well-being. One of the supporting predictors on resilience is Psychological well-being and religiosity. The Psychological well-being has important role to increase self resilience, and religiosity has a role related to Psychological well-being to increase resilience. This research aims to find out the role of religiosity and psychological well-being to Resiliencen women who struggle in domestic violence. Research method was based correlation design.We used Religiosityscale by Glock and Stark and RPWB (Ryff's Psychological Well-being) and Resilient Question scale by Reivich and Shatte.Population in this research was victim of domestic violence and sample was 62 women who was victim of domestic violence based on purposive sampling methods.The Analysis test result used regression that R-squared = 0,11 (p > 0,05) for religousity and resilence. R-squared 0.59 (p>0.05) for PWB and resilence. It means there is significant contribution of religiosity and Psychological well-being to resilience on women who were victims of domestic violence.This result are expected that government and domestic violence institution can practically improve the religiosity and Psychological well being of victims of domestic violanceto increase resilience.